Epidemiology of basal and cutaneous squamous cell carcinoma in the U.K. 2013–15: a cohort study. (6th May 2019) - Venables, Z.C.; Nijsten, T.; Wong, K.F.; Autier, P.; Broggio, J.; Deas, A.; Harwood, C.A.; Hollestein, L.M.; Langan, S.M.; Morgan, E.; Proby, C.M.; Rashbass, J.; et al.
Summary: Background: Basal cell carcinoma (BCC) and cutaneous squamous cell carcinoma (cSCC), together known as keratinocyte cancers (KCs), are the commonest cancer in white ethnic populations. Recent improvements to registry data collection in England has allowed more accurate analysis of the epidemiology of BCC and cSCC and for the first time we are able to provide an accurate (representative) tumour burden for KC in the U.K. Objectives: To estimate the incidence of BCC and cSCC in the U.K. Methods: A cohort of patients with KCs between 2013 and 2015 were identified using linkage to diagnostic codes derived from pathology reports collected into the national cancer registry. Data from England's cancer registry were combined with data from Scotland, Northern Ireland and Wales. European age‐standardized incidence rates (EASRs) of the first BCC and cSCC per patient per annum (PPPA) were calculated. Results: In the U.K, the EASR of the first BCC and cSCC PPPA in 2013–15 were 285 and 77 per 100 000 person years, respectively (211 120 KCs total in 2015). The mean annual percentage increase was 5% between 2013 and 2015 for both BCC and cSCC. By counting the first KC PPPA, we include an additional 51% KCs compared with the previous reporting technique which counts only the first BCC and cSCC in a patient's lifetime, yet it represents a probable underestimation of 5–11% of the true tumour count. Conclusions: Based on an improved methodology, a more representative incidence of KC is presented, which is essential to healthcare planning and will lead to improved understanding of the epidemiology of KC. What's already known about this topic? Keratinocyte cancers (KCs) are the most common cancers affecting white ethnic populations. The incidence of basal cell carcinoma (BCC) and cutaneous squamous cell carcinoma (cSCC) is increasing worldwide including the U.K., most commonly in elderly male Caucasian patients. These cancers are traditionally substantially underreported and frequently excluded from national cancer statistics. What does this study add? Using improved data collection methods in England and validated tumour‐reporting techniques, we report the most accurate BCC and cSCC incidence data for the U.K. ever published. Identifying the first BCC and cSCC per patient per annum, the incidence of BCC and cSCC in the U.K. (excluding Wales) was 285 and 77 per 100 000 person years, respectively, between 2013 and 2015, with more than 210 000 KCs in the U.K. in 2015. Abstract : Linked Editorial : Whiteman. Br J Dermatol 2019; 181 :434–435 . Plain language summary available online Respond to this article